Analysis of Human Resources (HR) Development Strategy and Mitra Asri Insurance Products in Increasing Competitive Advantage: Case Study at PT. Asuransi AJB Bumiputera 1912 Medan Branch - M. Yusuf; Zainarti; Budi Harianto (Jurnal Manajemen Bisnis, 2024)
This study delves into the strategic analysis of resource development for human capital (SDM) and the insurance product, Mitra Asri, in enhancing competitive advantage. The case study centers on PT. AJB Bumiputera 1912 Insurance, specifically its Medan branch. The research investigates the strategies implemented by the company to develop its human resources and promote the Mitra Asri insurance product. Through comprehensive analysis and evaluation, this study aims to uncover the correlation between the development of human resources and the market success of the Mitra Asri insurance product within the competitive landscape. The findings aim to provide insights into effective strategies for enhancing competitive advantage through human resource development and product promotion in the insurance industry. The problem that will be discussed in this research is the strategy for developing human resources and developing Mitra Asri insurance products at PT. AJB Bumiputera Insurance 1912 Medan Branch. The purpose of this research is to determine the HR development strategy and Mitra Asri insurance products used by PT. AJB Bumiputera 1912 Insurance in increasing competitive advantage.